Quantitative analysis of anatomical relationship between cavernous segment internal carotid artery and pituitary macroadenoma. Issue 41 (October 2016) - Lin, Bon-Jour; Chung, Tzu-Tsao; Lin, Meng-Chi; Lin, Chin; Hueng, Dueng-Yuan; Chen, Yuan-Hao; Hsia, Chung-Ching; Ju, Da-Tong; Ma, Hsin-I; Liu, Ming-Ying; Tang, Chi-Tun
Abstract : Abstract: Cavernous segment internal carotid artery (CSICA) injury during endoscopic transsphenoidal surgery for pituitary tumor is rare but fatal. The aim of this study is to investigate anatomical relationship between pituitary macroadenoma and corresponding CSICA using quantitative means with a sense to improve safety of surgery. In this retrospective study, a total of 98 patients with nonfunctioning pituitary macroadenomas undergoing endoscopic transsphenoidal surgeries were enrolled from 2005 to 2014. Intercarotid distances between bilateral CSICAs were measured in the 4 coronal levels, namely optic strut, convexity of carotid prominence, median sella turcica, and dorsum sellae. Parasellar extension was graded and recorded by Knosp–Steiner classification. Our findings indicated a linear relationship between size of pituitary macroadenoma and intercarotid distance over CSICA. The correlation was absent in pituitary macroadenoma with Knosp–Steiner grade 4 parasellar extension. Bigger pituitary macroadenoma makes more lateral deviation of CSICA. While facing larger tumor, sufficient bony graft is indicated for increasing surgical field, working area and operative safety.